The Relationship Between Vegetable and Fruit Consumption and Physical Activity On Nutritional Status In Adolescents - novi, Novianty; Rahmi Garmini (IKesT Muhammadiyah Palembang, 2025)
Background : The problem of nutritional status in adolescents is caused by an imbalance between intake and needs, which will cause undernutrition problems or overnutrition problems. One of the other factors that affects nutritional status is a lack of physical activity. Poor nutrition in adolescents and adults causes a lack of energy availability, so they get tired easily, certain diseases appear, and productivity decreases. Meanwhile, nutritional conditions increase the risk of non- communicable diseases such as cardiovascular disease, metabolic syndrome, and cancer. Research Objective: To determine the relationship between vegetable and fruit consumption, physical activity, and nutritional status in adolescents. Research Method: This quantitative study uses a cross-sectional study design located at SMK 3 Muhammadiyah Palembang in February-May 2024. Data was collected through height and weight measurements, and questionnaires were filled out. The research instruments used were a semi-quantitative FFQ-form questionnaire and a short-form version of the International Physical Activity Questionnaire, which used an interview method. A static test to analyze the relationship between variables is the Chi-square test. Results: There was a relationship between vegetable and fruit consumption, physical activity, and nutritional status in adolescents (p-value < 0.05). Conclusion: The better vegetables and fruits are consumed, the better the nutritional status of adolescents will also be. The more physical activity teenagers do, the better their nutritional status will be. Sufficient consumption of vegetables and fruits and good physical activity will help adolescents achieve optimal growth and development.